On the possible mechanisms of a positive effect on the retina of goggles with red filters in premature infants - M. V. Zueva; O. A. Ushnikova; L. A. Katargina (Российский офтальмологический журнал)
In recent publications, positive results have been reported with the use of glasses with red protective filters in prematurely born infants with low body weight, which were presumably associated with a decrease in the levels of illumination of the environment of the child. However, to date, it has not been proven that a decrease in the amount of light reaching the retina of the newborn affects the frequency and severity of retinopathy of prematurity (RP). The analysis of the literature on the therapeutic effect of various modes of red and near infrared radiation on the retina is presented, which allowed a different look at the protective mechanisms of glasses-filters in premature babies. It has been suggested and substantiated that the observed effect may relate to the phenomenon of pre-conditioning photostimulation, which reduces the risk of developing RP and reduces the severity of the disease due to the induction of adaptive plastic reactions in the retina.